High‐fat diet–induced alterations to gut microbiota and gut‐derived lipoteichoic acid contributes to the development of enteric neuropathy. Issue 7 (13th March 2020) - Nyavor, Yvonne; Brands, Catherine R.; May, George; Kuther, Sydney; Nicholson, Jessica; Tiger, Kathryn; Tesnohlidek, Abigail; Yasuda, Allysha; Starks, Kiefer; Litvinenko, Diana; Linden, David R.; Bhattarai, Yogesh; et al.
Abstract: Background: High‐fat diet, microbial alterations and lipopolysaccharide (LPS) are thought to cause enteric diabetic neuropathy and intestinal dysmotility. However, the role of the gut microbiota, lipoteichoic acid (LTA) from Gram‐positive bacteria and short‐chain fatty acids (SCFAs) in the development of diabetic enteric neuropathy and intestinal dysmotility is not well understood. Our aim was to examine the role of the gut microbiota, LTA and SCFAs in the development of diabetic enteric neuropathy and intestinal dysmotility. Methods: We fed germ‐free (GF) and conventionally raised (CR) mice either a high‐fat (HFD) or standard chow diet (SCD) for 8 weeks. We analyzed the microbial community composition in CR mice using 16S rRNA sequencing and damage to myenteric neurons using immunohistochemistry. We also studied the effects of LPS, LTA, and SCFAs on duodenal muscularis externa contractions and myenteric neurons using cultured preparations. Key Results: High‐fat diet ingestion reduced the total number and the number of nitrergic myenteric neurons per ganglion in the duodenum of CR but not in GF‐HFD mice. GF mice had fewer neurons per ganglion compared with CR mice. CR mice fed a HFD had increased abundance of Gram‐positive bacteria. LTA and LPS did not affect the frequency of duodenal muscularis contractions after 24 hours of cultured but reduced the density of nitrergic myenteric neurons and increased oxidative stress and TNFα production in myenteric ganglia. SCFAs did not affect muscularis contractions or injure myenteric neurons. Conclusions & Inferences: Gut microbial alterations induced increase in Gram‐positive bacterial LTA may contribute to enteric neuropathy. Abstract : A high‐fat diet alters the gut microbial community in conventionally raised mice, leading to an increase in Gram‐positive Firmicutes. This increase in Gram‐positive bacteria is likely associated with increased lipoteichoic acid (LTA). LTA induces enteric neuropathy, which is associated with increased neuroinflammation and oxidative stress in the gastrointestinal tracts of mice fed a high‐fat diet.